Słowo magiczne jako działanie – o kilku walorach koncepcji Bronisława Malinowskiego - Rakoczy, Marta (Wydawnictwo Naukowe UAM, 2013)
This article concerns Bronisław Malinowski’s ethnographical theory of magical word. His theory was a revolutionary one for two reasons (1) he claimed that magical word is not an instrument of understanding of „primitive mentality” (2) he argued that analysis of magical word demanded abandoning of textual bias which entailed our seeing linguistic genres as semantically autonomous texts. Malinowski was not so interested in the question of literacy. He remarked, though, that writing determinated our linguistic reflection and that magical word, as another oral linguistic genres, demanded a radical rejection of textual conceptions of meaning, language and folklore. Although Malinowski’s methodological stipulations were not always consistent and his rejection of textual bias was fairly half, his abandonment of the conception of „magical world view” which is a foundation for uses of magic is still up-to-date.
Magical Word as an Action. A Few Thoughts about Bronisław Malinowski’s Concepts
Keywords: magical word; literacy; textual bias; textualisation; „magical world view”